2010
DOI: 10.1186/1471-2164-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate, aspartate and nucleotide transporters in the SLC17 family form four main phylogenetic clusters: evolution and tissue expression

Abstract: BackgroundThe SLC17 family of transporters transports the amino acids: glutamate and aspartate, and, as shown recently, also nucleotides. Vesicular glutamate transporters are found in distinct species, such as C. elegans, but the evolutionary origin of most of the genes in this family has been obscure.ResultsOur phylogenetic analysis shows that the SLC17 family consists of four main phylogenetic clades which were all present before the divergence of the insect lineage. One of these clades has not been previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 52 publications
2
40
2
Order By: Relevance
“…Relatively high levels of VNUT mRNA and/or VNUT immunoreactivity are present in the stomach, intestine, liver, lung, skeletal muscle, thyroid, spleen, blood cells, chemosensory epithelial cells, and keratinocytes [35,[37][38][39][40], suggesting that VNUT-mediated nucleotide entry into the secretory pathway is not restricted to the brain and neuroendocrine tissues. Indeed, VNUT has emerged as a widely expressed nucleotide transporter responsible for the uptake of ATP into secretory granules and vesicles, consequently, contributing to the release of ATP (and likely other nucleotides) from the secretory pathway in a variety of physiologically relevant conditions.…”
Section: Cellular Release Of Nucleotides From the Secretory Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively high levels of VNUT mRNA and/or VNUT immunoreactivity are present in the stomach, intestine, liver, lung, skeletal muscle, thyroid, spleen, blood cells, chemosensory epithelial cells, and keratinocytes [35,[37][38][39][40], suggesting that VNUT-mediated nucleotide entry into the secretory pathway is not restricted to the brain and neuroendocrine tissues. Indeed, VNUT has emerged as a widely expressed nucleotide transporter responsible for the uptake of ATP into secretory granules and vesicles, consequently, contributing to the release of ATP (and likely other nucleotides) from the secretory pathway in a variety of physiologically relevant conditions.…”
Section: Cellular Release Of Nucleotides From the Secretory Pathwaymentioning
confidence: 99%
“…Knocking down SLC17A9 by small interfering RNA (siRNA) decreased KCl-triggered ATP release in PC12 cells [37]. In situ hybridization studies indicated that SLC17A9 transcripts are widely expressed in the brain, with particularly high levels of expression in regions of the hippocampus known to display purinergic neurotransmission [35].…”
Section: Cellular Release Of Nucleotides From the Secretory Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Since VNUT was reported to be expressed in various tissues, including the lung (25), we hypothesized that VNUT mediates nucleotide uptake in airway epithelial cell mucin granules, thereby contributing to the release of nucleotides from mucinsecreting goblet cells. In this study, we used Calu-3 cells as a model of airway epithelial goblet cells (8,9) to investigate the expression of VNUT in mucin granules and further examined VNUT's contribution to mucin granule nucleotide content and release.…”
mentioning
confidence: 99%
“…Active plasmalemmal transport of ATP is associated with ABC transporters that are expressed already in protists [221]. Finally, exocytotic ATP release that uses vesicles bearing specific nucleotide transports (VNUT/SLC17A9) allows spatially restricted and tightly regulated ATP release characteristic for nervous system, the VNUT-bearing vesicles are found in invertebrates and characterized in the nematode C. elegans, in sea anemone, in sea urchin and in some insects [222,223]; they are present in vertebrates, where they are expressed in various tissues including the brain [215].…”
Section: Ca 2þ As a Regulator Of Programmed Cell Deathmentioning
confidence: 99%